2020
DOI: 10.15789/2220-7619-ado-1186
|View full text |Cite
|
Sign up to set email alerts
|

Advancing diagnostics of chronic paradontitis in children

Abstract: Chronic periodontitis in children and adolescents holds a lead place in morbidity pattern of dental pathology. Development of chronic periodontitis is accompanied by emergence of various complications in the maxillofacial region, leading to bite disturbance being of high relevance for pediatric patients. These and other complications are related to immune system immaturity in children and adolescents as well as virulence of microorganisms. However, the immunological changes developing in children with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Bacteria can thus enter the bloodstream and spread throughout the body, affecting organ function. It has been suggested that bacteria and their products, rather than bacteria themselves, activate the body’s monocytes/macrophages and produce a large number of inflammatory factors ( Agarkov et al, 2020 ), including endotoxin, LPS, pore proteins, and polysaccharides. In addition to this, the membrane vesicles (MVs) discovered in recent decade seem to have the similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria can thus enter the bloodstream and spread throughout the body, affecting organ function. It has been suggested that bacteria and their products, rather than bacteria themselves, activate the body’s monocytes/macrophages and produce a large number of inflammatory factors ( Agarkov et al, 2020 ), including endotoxin, LPS, pore proteins, and polysaccharides. In addition to this, the membrane vesicles (MVs) discovered in recent decade seem to have the similar effect.…”
Section: Introductionmentioning
confidence: 99%